Catecholamine-induced cardiomyopathy and multiple organ failure in pheochromocytoma - Joel Thekekara; Atchayaa Gunasekharan; Young Kwon; Niaz Memon; Joe N Hackworth (Greater Baltimore Medical Center, 2020)
A 55-year-old Caucasian woman with no significant past medical history presented with chest pain, palpitations, shortness of breath, and nausea. Physical examination was notable for a blood pressure of 182/87 mmHg, heart rate (HR) of 74 beats per minute (bpm), temperature of 98.3ºF, and oxygen saturation of 94% on 15 liters (L) of oxygen per minute. Her initial labs revealed troponin of 0.26 ng/mL (<0.01 ng/mL), blood glucose of 497 mg/dL (70-99 mg/dL), lactic acid of 6.9 mmol/L (0.4-1.9 mmol/L), and white blood cell (WBC) of 21.6 K/uL (4-11.0 K/uL). EKG showed ST elevation in leads V1 and V2. CT Pulmonary angiography with contrast ordered to rule out pulmonary embolism revealed a right adrenal mass measuring 3.5 cm x 4.1 cm. Patient was admitted to the intensive care unit for ST elevation myocardial infarction, hyperglycemia, and sepsis. She was started on heparin, broad-spectrum antibiotics, intravenous fluids, and insulin. Emergent echocardiogram revealed 40-45% ejection fraction with septal, lateral, anteroseptal, and posterolateral hypokinesis. Troponin elevation to 1.00 ng/mL (<0.01 ng/mL) warranted a cardiac angiography which revealed new-onset systolic heart failure with reduced ejection fraction with normal coronary vessels. A relatively rapid improvement in her clinical course suggested that a functioning tumor could be the underlying etiology. Diagnostic work-up for pheochromocytoma showed elevated metanephrine and normetanephrine. Subsequent surgical biopsy of the adrenal mass was consistent with pheochromocytoma. It was a rare case presentation of pheochromocytoma with catecholamine-induced cardiomyopathy and multiple organ failure.